Conception of purposes of learning in preschool-age - Raižienė, Saulė; Endriulaitienė, Auksė; Ormerod, Jurgita (Psichologija, 2007)
Learning begins early in life; so do children’s beliefs and attitude towards learning. Much is known about how children learn in general as well as in specific domains, however, little is known about the early beginnings and development of academic purposes. The aim of this study was to discover how preschoolers understand the reasons for learning. Two studies were done to achieve this goal. 121 children participated in the first study which tried: 1) to compare the understanding of reasons for learning of four- and six-year-old children and 2) to compare the understanding of reasons for learning of boys and girls in preschool age. Sixty-two children took part in the second study which examined the perception of reasons for learning of five-year-old children living in the country and in a city. All data were collected using the following methods: „Cow scenario“ (Li, 2004a), „School stories“ (Wang and Leichtman, 2000), „Birthday book probing“ (Li, 2004a). Two types of variables, reflective and content, were examined. The results of the first study revealed that already four-year-old children have their opinion about the learning process and school. Their attitude towards learning changes as children grow up. Younger children appeared to have already developed some basic understandings of reasons for learning, although elder children showed much more consistent patterns than their younger peers. Analysis of children’s answers by content variables shoved that younger and elder children identified the following types of benefits from learning: intellectual, economic, and social (for the benefit of others). They have a positive attitude to the learning process and can formulate the positive emotional effect of learning. However, six-year-old children name the categories of intellectual and economic benefit and the value expression more often than their younger peers. The boys’ and girls’ attitude towards learning was very similar. The results of the second study revealed that there was a difference in understanding the social benefit and gaining knowledge/skill among five-year-old children living in a village and in a city.